Global, Continental, and Regional Development Agendas – What Does It Mean to Domesticate or Localise These? - Lusanda Batala (The Thinker)
The domestication of regional, continental and global development agendas can be confusing, leading to one concluding that these are either an addition to or a replacing of, a country's national development plan. What do these various development agendas mean for a country like South Africa versus the country's domestic development focus as espoused in the National Development Plan (NDP)? What does domestication of the various agendas mean? The key idea to note here is that domestication is not about replacing a country's development agenda with a regional or continental or global development agenda. What is important is to ensure that there is alignment of the domestic plan (objectives, priorities) with those of the rest of the world, the continent and the region.  Global, continental and regional agendas are not separate programmes. They are part of the National Development Plan. South Africa's implementation of its own development plan indirectly implements other development agendas.